Temporal Variation of Treatment Patterns and Survival Outcomes of Triple-Negative Breast Cancer Patients: A Real-World Experience From 2000 to 2014 - Valcarcel, B (2023)
Background: Previous studies have reported a higher prevalence of triple-negative breast cancer (TNBC) in US Hispanic/Latina populations. However, survival outcomes and treatment approaches over time in Latin American females are scarcely reported. We aimed to evaluate the temporal variation in treatment patterns and overall survival (OS) outcomes of females with TNBC according to cancer stage. Materials and Methods: We performed a single-center retrospective cohort study on 1840 females from 2000 to 2014. Patients were classified in 3 calendar periods (2000-2004, 2005-2009, and 2010-2014). The Kaplan-Meier method and multivariable regression analyses were employed. Results: Stage III cancer was identified in half of the population. Five-year OS estimates for cancer stages I, II, and IV remained unchanged across all calendar periods. However, we found worsening 5-year OS estimates in stage III females (49% in 2000-2004 and 31% in 2010-2014; P < .001). Despite increased uptake of overall use of neoadjuvant therapy in stage III females, the time from diagnosis to treatment initiation (P = .013) and time to complete the planned cycles (P < .001) increased over time. Fifty-sex percent of stage IV patients were untreated. Females aged ≥70 years were less likely to receive treatment. Conclusions: Survival estimates were lower than those reported in high-income countries. Most females were diagnosed with advanced disease, and the OS for stage III females worsened over time. Our outcomes show difficulties in delivering timely neoadjuvant therapy in an overwhelmed healthcare system. Public health authorities should improve screening practices, develop regional clinical guidelines, and expand trial enrollment.